Pathogenic mechanisms and molecular features of a novel UL2 gene-deficient duck enteritis virus endemic to China - Dan Yin; Yuehua Gao; Mingqing Xu; Jianhua Wang; Xiaofei Song; Zhen Li; Jianyun Peng; Min Kang; Bai Wei; Chengdong Yu; Yingjuan Qian; Yong-Sam Jung; et al. (Virulence)
Duck enteritis virus (DEV) was identified as the etiological agent responsible for an outbreak of morbidity and mortality in adult ducks on a farm in Jiangsu, China. Diagnostic approaches confirmed that the outbreak was caused by the highly pathogenic DEV-JS2024 isolate. The clinical progression of the disease, characterized by lethargy, anorexia, ocular discharge, and high mortality, was accompanied by extensive hemorrhagic lesions in critical organs such as the liver, spleen, lungs, and bursa of Fabricius, consistent with known signs of DEV infection. Genomic analysis of DEV-JS2024 revealed a 45% G+C content and 76 open reading frames. BLASTn analysis revealed that the genome of DEV-JS2024 shares the highest sequence similarity with the Chinese virulent strain CV and the DEV attenuated vaccine strain C-KCE in the database. These results indicate a close genetic relationship between DEV-JS2024 and both the virulent and attenuated strains, suggesting potential similarities in their genomic architecture. Comparative genomic analysis identified 28 nucleotide mutations, including 15 non-synonymous mutations potentially related to virulence factors. The study also highlighted the first reported 528 base pairs deletion in the UL2 gene of a virulent strain, challenging its utility as a marker for distinguishing virulent from attenuated strains. Phylogenetic analysis suggested that DEV-JS2024 May result from recombination between the vaccine and virulent strains, further complicating our understanding of DEV pathogenicity. This study provides new insights into the molecular evolution of DEV and stresses the importance of continued genomic surveillance to enhance vaccine development and control measures for duck plague.